Impact of Droplets on Surfaces Designed with Wettability-Gradient Properties Directional Migration, Oblique Rebound, and Reduced Contact Time - Li, Tao (Langmuir : the ACS journal of surfaces and colloids, 2024)
Efficiently regulating the rebound behavior of droplets post-impact is crucial for various fields, mainly including the development of self-cleaning applications, the design of surface functional materials, and the advancement of industrial techniques. By performing molecular dynamics simulations, we investigated the impact and jumping behavior of droplets on heterogeneous substrates with different wetting regions. We found that, during the impacting evolution process, the retracted droplets would move toward regions with stronger wettability due to the unbalanced force caused by the wettability difference, revealing the directional migration ability. The values of the wettability difference strongly affect the degree of oblique rebound and contact time when droplets can jump off the substrate. We then designed the surfaces with a wettability gradient and found that the oblique rebound angle could be well controlled and the contact time further reduced. Our findings may provide valuable insight into the relationship between the wettability gradient and the behavior of liquid droplets on surfaces, with broad implications for various fields such as surface engineering, materials science, microfluidics, etc